2016
DOI: 10.1111/1556-4029.13131
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Indicators of Stress: A Component of the Biocultural Profile of Undocumented Migrants in Southern Arizona,

Abstract: The ability of forensic anthropologists in the United States to distinguish the remains of foreign nationals from those of American citizens may be crucial to the identification process. This study adds new criteria for identifying Hispanic foreign nationals in southern Arizona to those previously outlined by Birkby et al. (J Forensic Sci 53, 2008, 29) in the "cultural profile." Skeletal indicators of nonspecific stress were evaluated in undocumented border crossers (UBCs) at the Pima County Office of the Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 41 publications
1
56
1
Order By: Relevance
“…The higher frequency of PCLs among individuals who died of natural causes relative to other causes supports the interpretation of CO and PH as indicators of physiological stress. Individuals who die from accidents, homicides, or suicides are not necessarily suffering from infectious maladies or physiological stress (see Beatrice & Soler, 2016 for a discussion of psychosocial stress and PCLs). Therefore, these MOD are not expected to have higher prevalence of PCLs related to physiological stress compared to the sample as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…The higher frequency of PCLs among individuals who died of natural causes relative to other causes supports the interpretation of CO and PH as indicators of physiological stress. Individuals who die from accidents, homicides, or suicides are not necessarily suffering from infectious maladies or physiological stress (see Beatrice & Soler, 2016 for a discussion of psychosocial stress and PCLs). Therefore, these MOD are not expected to have higher prevalence of PCLs related to physiological stress compared to the sample as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health outcomes explored included psychological distress, depression (i.e., depressive symptoms, major depressive disorder (MDD)), anxiety (i.e., anxiety symptoms, generalized anxiety disorder (GAD), panic disorder (PD), trauma- and stressor-related disorders (i.e., post-traumatic stress disorder (PTSD), adjustment disorder, acute stress disorder (ASD)), substance use/abuse (i.e., alcohol and drug use), psychiatric symptoms, and self-rated mental health. One study investigated physiological stress as assessed through skeletal remains of UIs found in the desert ( Beatrice and Soler, 2016 ). Other mental health outcomes explored were satisfaction with life, flourishing, sense of safety, fear, despair, anger, shame, health-related quality of life, self-reported health, sleep difficulties, general wellbeing, and resilience.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, many of the Latina/o/x individuals analyzed in the southwestern United States are not actually “U.S. Hispanic” decedents but rather Latin American migrants who may have population histories—and embodied social histories [6,39]—that render them genetically and morphologically distinct from U.S.‐born Latina/o/x individuals [28]. While the recognition of these groups’ genetic and morphological complexities is a key aspect of our recent disciplinary advancement, the discipline still has work to do: for example, accounting for these micro‐level population differences rather than pooling them into the unitary social ethnicity category of “Hispanic.” Further, the dedicated research focus recently extended to “complex” Latina/o/x populations should also be given to other groups with complex population histories [3].…”
Section: Discussionmentioning
confidence: 99%